THE EFFECT OF SUBCUTANEOUS EPINEPHRINE DOSAGE ON BLOOD LOSS IN SURGICAL INCISION - Naz, Erum; Ali Khan, Faisal Akhlaq; Zulfiqar, Bushra; Farrukh, Rabeeaa; Naseem, Aiman; Isamail, Sarosh (Journal of Ayub Medical College Abbottabad, 2024)
Background: Vasoconstrictive drugs are increasingly frequently used to stop bleeding during cosmetic and reconstructive surgeries, especially subcutaneous epinephrine7. As far as we are aware, no studies have been conducted on how adrenaline affects bleeding in patients having supraventricular flap surgery so we planned this study to find out the impact of various epinephrine dosages on the amount of bleeding in surgical incisions among participants undergoing supraclavicular flap surgery. Methods: This single-blinded randomized controlled trial was performed at the Department of Plastic Surgery, Ruth Pfau Civil Hospital, from September 2022 to September 2023. Group 1 was given 0.9% saline with an epinephrine concentration of 1:200,000. Group 2 was administered a 0.9 % saline solution containing a 1:400,000 epinephrine concentration. Group 3 was given just 10 ml of 0.9 % saline (control group). Bleeding was measured for 5 minutes by volumetric method. Results: Patients’ age (p=0.221), gender (p=1.000) and surgery site (p=0.265) were not significantly different among the three study groups. Mean blood loss volume for group 1, group 2 and group 3 was 15.8 0±5.37mL, 19.80±8.44mL and 57.20±14.14mL respectively. On post-hoc analysis for total blood loss volume, significant differences were seen between Group 1 and Group 3 (p<0.001), and Group 2 and Group 3 (p<0.001). Conclusion: The present study showed that blood loss was significantly lower among both of the groups of adrenaline but blood loss from the two doses of epinephrine did not differ significantly.